Addressing violence against transgender people in Bangladesh: A call for policy intervention - Barua, Arup; Khan, Shehreen Ataur (Frontiers in Sociology, 2023)
Violence, oppression, and cruelty are as old as human civilization itself. Human identity is multi-layered, and deviation from a specific identity may elicit violence, deprivation, and prejudice in various settings. In many countries and societies, the transgender community is one of the most vulnerable groups due to their gender incongruence. Deeply ingrained cultural norms, beliefs, social ignorance, and practices have transferred violence against transgender people over generations, preventing them from enjoying their fundamental human rights. Key objectives of this article are 2-fold: first, this article focuses on violence against transgender people and rights violation in Bangladesh; and second, the report examines the types of violence against the transgender population and the actors who must be involved in providing a solution. Moreover, this article unravels the current organizational and institutional advances in supporting the welfare and rights of the transgender community in Bangladesh. This article concludes that the absence of a dedicated national policy for the protection and welfare of the transgender population impedes the implementation of necessary measures, which should be facilitated by formulation of an appropriate policy, followed by effective implementation.